Nursing Competency: Mediating Burnout, Coaching, and Documentation Completeness in Bekasi General Hospital - Slamet Yuliono; Nofierni Nofierni; Sandra Dewi (Global Management: International Journal of Management Science and Entrepreneurship, 2026)
The completeness of nursing care documentation serves as a primary indicator of hospital service quality and remains a critical component of patient safety, clinical communication, and legal accountability. Despite its importance, empirical evidence from various healthcare facilities indicates that nursing records are frequently suboptimal, incomplete, or inconsistent. This study aims to analyze the complex interrelationships between burnout and coaching on the completeness of nursing care documentation, specifically examining the role of nursing competence as a mediating (intervening) variable at the Dr. Chasbullah Abdulmadjid General Hospital in Bekasi City. Utilizing a quantitative research framework with a cross-sectional design, this study sampled practicing nurses stationed across inpatient and intensive care units. Primary data were gathered through a validated, structured questionnaire designed to measure psychological burnout, the frequency of clinical coaching, perceived professional competence, and the objective completeness of documentation. The data were subjected to rigorous analysis using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the hypothesized pathways within the conceptual model. The results demonstrated that burnout exerts a significant negative influence on both nursing competence and the quality of documentation, suggesting that emotional exhaustion hinders professional performance. Conversely, systematic coaching was found to have a significant positive impact, directly improving both competence levels and documentation adherence. Critically, the analysis confirmed that nursing competence acts as a vital intervening variable; it effectively mediates and strengthens the influence of both burnout reduction and coaching interventions on the overall completeness of nursing care records. This study concludes that proactive burnout management and the institutionalization of structured coaching programs are essential strategic priorities. By addressing these factors, hospital management can enhance individual nurse competence, thereby ensuring high-quality, comprehensive nursing documentation that supports patient safety and institutional integrity.